2000
DOI: 10.1016/s0550-3213(00)00486-7
|View full text |Cite
|
Sign up to set email alerts
|

Single pion production in neutrino reactions and estimates for charge-exchange effects

Abstract: We calculate single pion production by neutrinos in the resonance region. We consider both charged and neutral current reactions on free protons and neutrons. We present differential and total cross sections which can be compared with experiments. Then we use these results to calculate the spectra of the emerging pions including the Pauli suppression factor and rescattering corrections for reactions in heavy nuclei. Our results will be useful for studying single pion production and for investigating neutrino o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…It would be interesting to compare these results with earlier calculations of neutrino-induced pion production on nuclei by Paschos et al [11]. However, these authors have very recently found an error in their elementary pionproduction spectra [82] which affects their Figs.…”
Section: Pion Productionmentioning
confidence: 78%
See 1 more Smart Citation
“…It would be interesting to compare these results with earlier calculations of neutrino-induced pion production on nuclei by Paschos et al [11]. However, these authors have very recently found an error in their elementary pionproduction spectra [82] which affects their Figs.…”
Section: Pion Productionmentioning
confidence: 78%
“…8-14 for the pion energy distribution in Ref. [11]. In view of this we abstain from a comparison until the corrected results are published.…”
Section: Pion Productionmentioning
confidence: 99%
“…Recently Lee and Sato [5] have developed a new model for weak production of the Ll resonance. Paschos and collaborators [6] have also contributed to this effort. It is noteworthy that the theoretical and exper imental picture of the resonance region is far more obscure than the quasi-elastic and deep-inelastic scattering (DIS) regions which border it and that much of the relevant MINOS event sample falls inside this poorly-understood resonance region.…”
Section: · 223 Resonances and Transition To Deep-inelastic Scatteringmentioning
confidence: 99%
“…and (4) where (5) The recoil factor free is given by (6) 48 R(W) is the familiar Breit-Wigner expression [77] for the line-shape as a function of energy:…”
Section: Ge=gomentioning
confidence: 99%
See 1 more Smart Citation